Integrating OER in the design of educational material: Blended learning and linked-open-educational-resources-data approach - Piedra Pullaguari, N. (2016)
Teaching and Learning takes place in (or in a combination of) different educational environments: classroom, online, or mobile. Blended learning, or hybrid learning, is a formal educational program that integrates face-to-face learning with technology-based, digital instruction. On the other hand, Open Educational Resources (OER) provides a strategic opportunity to improve the quality of education as well as facilitate policy dialog, knowledge sharing, and capacity building. OERs are actual resources/tools that can help enrich any classroom environment and push student thinking and comprehension. One of the fundamental concepts of OER is "the ability to freely adapt and reuse existing pieces of knowledge", and therefore be a way to create more economic and personalized learning. The OER movement has challenged the traditional value chain by employing new methods to deliver high-quality educational content. The purpose of this work is to show a way to enhance the face-to-face classrooms with integration of OERs, and thus create blended learning instruction. Reuse of OERs by both individuals and organizations may have significant creative and economic benefit for learning environments. The approach is based on Linked Data for describe and publish OER. In this new paradigm for educational content consumption and integration, OER are expected to play a decisive and productive role for blended learning. The approach presented can be used to support different blended-learning models. © 2016 IEEE.